2001
DOI: 10.1007/s003300000741
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follow-up of GDC-treated saccular aneurysms by MR angiography

Abstract: The aim of this study was to determine sensitivity and specificity of magnetic resonance angiography (MRA) for the assessment of durable occlusion of intracranial aneurysms with Guglielmi detachable coils (GDC) and to point out the influence of MRA results in re-intervention strategies. Forty-five patients with 54 aneurysms that were previously treated by endovascular occlusion with GDC were selected for this study. All patients underwent digital subtraction angiography (DSA) and MRA examinations on the same d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…It has been reported that the sensitivity of MRA ranged from 0.76 to 0.98 32 and 0.92 with consensus reading. 33 We estimated sensitivity as 0.9 in this study, expecting that 1 or 2 of the 12 unaffected persons might be misclassified. To evaluate this uncertainty, linkage analyses with only affected members were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the sensitivity of MRA ranged from 0.76 to 0.98 32 and 0.92 with consensus reading. 33 We estimated sensitivity as 0.9 in this study, expecting that 1 or 2 of the 12 unaffected persons might be misclassified. To evaluate this uncertainty, linkage analyses with only affected members were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…However, iterative invasive angiography may have adverse effects, and the required duration of close surveillance remains to be determined. 36) Noninvasive MR angiography is currently limited due to metallic artifacts, 46) but advances in MR techniques, the study of large series, and long follow-up periods may increase the usefulness of this modality for the monitoring of such aneurysms.…”
Section: Relationships Of Aneurysm Size and Location To Outcomementioning
confidence: 99%
“…In dem für die Verlaufskontrolle wichtigsten Punkt, der Frage nach der Rekanalisation bzw. Reperfusion des Aneurysmas, geben verschiedene Autoren Sensitivitäten zwischen 72,7% und 92% sowie Spezifitäten zwischen 90,9% und 100% [1,4,5,16,26,27,32] an. Im Vergleich hierzu lagen die Sensitivität und Spezifität im eigenen Patientengut bei 90% bzw.…”
Section: Introductionunclassified